Comparative Study of Functional Grasp and Efficiency Between a 3D-Printed and Commercial Myoelectric Transradial Prosthesis Using Able-Bodied Subjects: A Pilot Study. Issue 3 (July 2017) - Duong, Tuan; Wagner, Brandon; Abraham, Tobin; Davidson, Michael; Bains, Gurinder; Daher, Noha; Friedrich, Alec
ABSTRACT: Introduction: Upper-limb amputations make up 10% to 20% of the total amputations in the United States. Of the two million individuals currently living with limb loss, 30% to 50% do not wear their prosthesis regularly. This is a result of lack of education, lack of training, discomfort, poor cosmetics, and cost. Three-dimensional (3D) printing may provide a cost-effective alternative for upper-limb prostheses. The purpose of this pilot study was to test and compare efficiency and functional capabilities of a 3D-printed and commercially available manufactured myoelectric hand. Materials and Methods: The research team designed a quasi-experimental, static group comparison trial. A box and blocks test was used to assess the efficiency of the i-limb and Limbitless Arm. The two prosthetic hands were tested over two visits with a 2-week crossover period. Two custom devices, to which the two hands attach distally, were created to accommodate the able-bodied subjects. Results: Twenty-four able-bodied (mean age, 26.1 ± 4.2 yrs), healthy, right-hand–dominant participants were recruited for this study. There were 14 men and 10 women. The mean number of blocks using the Limbitless Arm was significantly lower than the i-limb. For trial 1, the mean was 8.4 ± 3.6 versus 12.9 ± 3.3 ( P < 0.001). For trial 2, the mean was 8.3 ± 3.6 versus 13.8 ± 4.1 ( P < 0.001). Furthermore, the mean number of blocks improved when using the i-limb versus the 3D-printed hand by 53.6% in trial 1 and 66.3% in trial 2. Similar findings were obtained when we ran the analyses separately for men (trial 1, the mean was 9.1 ± 3.3 vs. 12.9 ± 3.7, P = 0.01 and trial 2, the mean was 9.6 ± 3.2 vs. 14.1 ± 4.7, P = 0.02) and women (trial 1, the mean 7.5 ± 3.9 vs. 12.8 ± 2.9, P = 0.00 and trial 2, the mean 6.3 ± 3.4 vs. 13.4 ± 3.2, P = 0.00). Conclusions: The results and observations made by the researchers suggested the i-limb was more efficient than the Limbitless Arm. There is a potential for 3D-printed prostheses to be a viable option for prosthetic care in the future with better development and technological advancements. However, at this point, myoelectric prostheses such as the i-limb are more practical and effective.